Aqueous biphasic systems composed of ionic liquids and sodium carbonate as enhanced routes for the extraction of tetracycline. (29th March 2013) - Marques, Carlos F. C.; Mourão, Teresa; Neves, Catarina M. S. S.; Lima, Álvaro S.; Boal‐Palheiros, Isabel; Coutinho, João A. P.; Freire, Mara G.
<x xml:space="preserve">Abstract</x> Aqueous biphasic systems (ABS) using ionic liquids (ILs) offer an alternative approach for the extraction, recovery, and purification of biomolecules through their partitioning between two aqueous liquid phases. In this work, the ability of a wide range of ILs to form ABS with aqueous solutions of Na2CO3 was evaluated. The ABS formed by IL + water + Na2CO3 were determined at 25°C, and the respective solubility curves, tie‐lines, and tie‐line lengths are reported. The studied ILs share the common chloride anion, allowing the IL cation core, the cation isomerism, the presence of functionalized groups, and alkyl side chain length effects to be evaluated. An increase in the cation side alkyl chain length leads to a higher ability for liquid–liquid demixing whereas different positional isomers and the presence of an allyl group have no major influence in the phase diagrams behavior. Quaternary phosphonium‐ and ammonium‐based fluids are more able to form an ABS when compared with imidazolium‐, pyridinium‐, pyrrolidinium‐, and piperidium‐based ILs. Moreover, the presence of an aromatic cation core has no major contribution to the formation of ABS when compared to the respective nonaromatic counterparts. Finally, to appraise on the systems applicability in downstream processing, selected systems were used for the partitioning of tetracyclines (neutral and salt forms) — a class of antibiotics produced by bacteria fermentation. Single‐step extraction efficiencies for the IL‐rich phase were always higher than 99% and confirm the great potential of ILs to be applied in the biotechnological field. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:645–654, 2013